Pemanfaatan Human Skin Equivalent (HSE) dalam Penelitian Patogenesis Skabies - Reqgi First Trasia (Neolectura, 2020)
Scabies is a tropical disease that requires large-scale control. Research on the pathogenesis of scabies in Indonesia is still rare. Meanwhile, in tropical countries, studies related to the course of scabies have been done quite a lot, one of which is by using a human skin model. The purpose of writing this article is to discuss the use of human skin modeling technology in researching the course of scabies. Research using HSE demonstrated modulation of cytokine secretion, expression of cell adhesion molecules, and gene expression in response to the scabies mite extract molecule.